Evaluasi Diameter Partikel Tanah Terhadap Derajat Kepadatan Tanah Menggunakan Metode Tekanan - Adyaksa, R. Nofan Hendra; Adha, Idharmahadi; Setyanto, Setyanto (Universitas Lampung, 2020)
Soil is a material to build any infrastructure. So, soil becomes very important and influential in construction. Soil quality determine the power of construction on it, the good soil is soil that has a high density in each particles and contain less water levels. The quality of soil is depending on physic and mechanic soil condition, that’s why we need to test it out. Soil compaction is process of increasing the soil density by reducing the particles proximity so it can reduce the air volume. Compaction is divided into four types. In this research is using two types of compactions that are type A and Type C with purpose to find out the effect of soil particles diameter by passing sieve analysis to soil compaction.Compaction is done based on blow method and pressure method. In pressure method is using modification compaction tool with 5 Mpa, 10 Mpa, and 15 Mpa pressures.The result of this research can be conclude that the blow method compaction type A has a higher water content than type C, but the value of maximctum dry volume weight Type C higher than type A. In pressure method it can be concluded that as the higher pressure so the water content and the maximum dry volume weight are also getting higher.